The Evaluation Model of Construction Enterprises Culture Development Based on FAHP - Wu, Xinhua; Jia, Hongjun (SHS web of conferences, 2015)
An evaluation method is presented to evaluate the effect of construction enterprises culture development. This paper gives a brief introduction to the connotation and path of construction enterprises culture, also the project-oriented characteristics of it. On this basis, the evaluation index system is given by the literature. Then the disadvantages of AHP are enumerated, and a more effective method of fuzzy analytical hierarchy process (FAHP) is presented, which is proved to be effective by a case.